Klasifikasi Alat Musik Tradisional Minangkabau - Sari, Dian Novita; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
Abstract The writing of this paper aims to (1) find out the classification of Minangkabau traditional musical instruments; (2) knowing the process of classifying Minangkabau traditional musical instruments; (3) knowing the obstacles and efforts to overcome obstacles in the process of classifying Minangkabau traditional musical instruments. Writing this paper using descriptive research methods. Data was collected based on observations and interviews from various sources. Based on the results of the study it can be concluded as follows, first classifying the traditional Minangkabau musical instrument the first step taken is data collection and data compilation. Then classify musical instruments based on the types of musical instruments which are divided into five, namely striking, blowing, striking, picking and pressing musical instruments, but there are only four types of musical instruments in Minangkabau, namely striking, blowing, striking and picking instruments. The types of musical instruments are classified according to the guidelines on DDC (dewey decimal classification). The two processes of classifying traditional musical instruments have several parts, as follows: (1) Dewey's classification; (2) Determine the Main Class; (3) Determine Divisions; (4) Determine the Section. The three obstacles in the process of classifying traditional Minangkabau musical instruments are as follows: (1) lack of information regarding musical instruments in the Minangkabau Region including the area of origin of the musical instruments; (2) the difficulty of grouping musical instruments based on the type of musical instrument, because many names of musical instruments are almost the same. Efforts to overcome obstacles in the process of classifying Minangkabau traditional musical instruments are as follows: (1) conducting the process of collecting all data derived from several literatures and institutions that store traditional Minangkabau musical instruments; (2) pay close attention to musical instruments to be grouped according to the type of music.Keywords: classification; traditional musical instruments; minangkabau